Exploring human behavior change in equine welfare: Insights from a COM-B analysis of the UK's equine obesity epidemic - Furtado, Tamzin; Perkins, Elizabeth; Pinchbeck, Gina; McGowan, Catherine; Watkins, Francine; Christley, Rob (Frontiers in Veterinary Science, 2022)
While equine obesity is understood by equine professionals to be a serious and widespread welfare problem, thus far approaches to reducing the prevalence of obesity in the UK’s leisure horses have mainly been limited to educating owners about the dangers of obesity in their horses. In human health, approaches to behaviour change encourage holistic thinking around human behaviour, recognising the importance of the connection between the individuals’ knowledge, attitudes, habits, and the social and physical environments. This study used qualitative data from interviews with horse owners and professionals, open-access discussion fora and focus groups in order to collate extensive information about the factors shaping the UK’s equine obesity crisis. The data were initially analysed using a grounded theory method to determine the common themes, and were then analysed using the COM-B model of behaviour change, in order to identify areas where human behaviour change might be better supported. The analysis highlighted the importance of a holistic approach to behaviour change, since all areas of the COM-B were important in limiting owners’ recognition of, and response to, equine obesity. For example, environments and social norms limited the likelihood of owners proactively managing horse weight, and owners also found it difficult to identify overweight horses, and evaluate the risks of long-term health issues as a result of weight, with short-term negative impacts of weight management. While interventions often aim to educate owners into changing their behaviour, this analysis highlights the importance of creative and holistic approaches which work alongside the owners’ motivations, while shaping the social and physical environments.